Woman standing by bookshelves - Unknown:::Creator::::::::::::
Photograph shows a smiling woman,who appears to be African American, standing by a shelving unit with books on it. She is at the Santa Clara Valley YWCA at 375 South Third Street, in San Jose, CA.